Development of the good health research practice course: ensuring quality across all health research in humans - Henley, Patricia; Horstick, Olaf (Health research policy and systems, 2017)
Quality and ethics need to be embedded into all areas of research with human participants. Good Clinical Practice (GCP) guidelines are international ethical and scientific quality standards for designing, conducting, recording and reporting trials involving human participants. Compliance with GCP is expected to provide public assurance that the rights, safety and wellbeing of participants are protected and that the clinical research data are credible. However, whilst GCP guidelines, particularly their principles, are recommended across all research types, it is difficult for non-clinical trial research to fit in with the exacting requirements of GCP. There is therefore a need for guidance that allows health researchers to adhere to the principles of GCP, which will improve the quality and ethical conduct of all research involving human participants. These concerns have led to the development of the Good Health Research Practice (GHRP) course. Its goal is to ensure that research is conducted to the highest possible standards, similar to the conduct of trials to GCP. The GHRP course provides training and guidance to ensure quality and ethical conduct across all health-related research. The GHRP course has been run so far on eight occasions. Feedback from delegates has been overwhelmingly positive, with most delegates stating that the course was useful in developing their research protocols and documents. Whilst most training in research starts with a guideline, GHRP has started with a course and the experience gained over running the courses will be used to write a standardised guideline for the conduct of health-related research outside the realm of clinical trials, so that researchers, funders and ethics committees do not try to fit non-trials into clinical trials standards.